2010
DOI: 10.2807/ese.15.34.19649-en
|View full text |Cite
|
Sign up to set email alerts
|

Case report: West-Nile virus infection in two Dutch travellers returning from Israel

Abstract: We report about West Nile virus (WNV) infections in a symptomatic traveller returning from Israel and in her asymptomatic travel companion. Knowledge of the current epidemiological situation in Israel from where WNV cases were reported recently enabled a rapid diagnosis. The described cases serve as a reminder for physicians to consider WNV in the diagnosis of patients returning from areas with potential circulation of the virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…This case report, like the recently described cases of West Nile fever imported from Israel to the Netherlands [16], emphasise the importance of surveillance also for potential imported cases of WNV infection. These imported cases serve as sentinels of the increase in the incidence of WNV disease occurring in 2010 in European and Mediterranean countries, where cases of WNV infection are notified every year, such as Romania (57 human cases in 2010), Hungary (three cases in 2010), Israel (24 cases in 2010), and Russia (480 cases in 2010) [14,[16][17][18][19]. Moreover, a large human epidemic outbreak with 261 confirmed cases of WNV disease occurred in Greece in 2010, where WNV infection had not been documented in humans before [20]; seven human cases of WNV infection were also confirmed in Turkey [21].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This case report, like the recently described cases of West Nile fever imported from Israel to the Netherlands [16], emphasise the importance of surveillance also for potential imported cases of WNV infection. These imported cases serve as sentinels of the increase in the incidence of WNV disease occurring in 2010 in European and Mediterranean countries, where cases of WNV infection are notified every year, such as Romania (57 human cases in 2010), Hungary (three cases in 2010), Israel (24 cases in 2010), and Russia (480 cases in 2010) [14,[16][17][18][19]. Moreover, a large human epidemic outbreak with 261 confirmed cases of WNV disease occurred in Greece in 2010, where WNV infection had not been documented in humans before [20]; seven human cases of WNV infection were also confirmed in Turkey [21].…”
Section: Discussionsupporting
confidence: 69%
“…Besides autochthonous human cases of WNV infection, we diagnosed a case of WNND imported from Romania, where an epidemic outbreak was ongoing with 57 human cases notified in 2010 [14]. This case report, like the recently described cases of West Nile fever imported from Israel to the Netherlands [16], emphasise the importance of surveillance also for potential imported cases of WNV infection. These imported cases serve as sentinels of the increase in the incidence of WNV disease occurring in 2010 in European and Mediterranean countries, where cases of WNV infection are notified every year, such as Romania (57 human cases in 2010), Hungary (three cases in 2010), Israel (24 cases in 2010), and Russia (480 cases in 2010) [14,[16][17][18][19].…”
Section: Discussionmentioning
confidence: 63%
“…A recent study in Italy linked to infected organ donors [8] draws the same conclusion, that the virus is being transmitted in areas previously thought to not be at risk or affected. Furthermore, the case report in this issue of a Dutch traveller returning from Israel with WN infection highlights the need for awareness among physicians and laboratory staff to consider WNV infections as a differential diagnosis in cases where patients return from areas where they may have been exposed to the virus [9].…”
mentioning
confidence: 99%
“…It was shown that and most recently a WNV infection was reported of a Dutch citizen returning from Israel [100]. These observations show that travelling in areas where WNV is endemic poses a risk for acquiring a WNV infection.…”
Section: Birdsmentioning
confidence: 87%